(untitled) (CAHIERS MAGELLANES-NS, 2024)
Epilepsy and Autism Spectrum Disorder (ASD) are neurodevelopmental conditions with notable comorbidity. This paper explores the overlapping pathways contributing to their co-occurrence and examines the therapeutic implications. By analyzing genetic, molecular, and neurophysiological mechanisms, we aim to provide insights into effective treatment strategies that address both disorders. The potential for integrated therapeutic approaches to improve patient outcomes is also discussed. Keywords Epilepsy, Autism Spectrum Disorder (ASD), Neurodevelopmental Disorders, Pathophysiology, Genetic Pathways, Neuroinflammation, Synaptic Dysfunction, Comorbidity, Seizures, EEG Abnormalities, Behavioral Manifestations, Cognitive Impairments, Therapeutic Interventions, Antiepileptic Drugs (AEDs) Behavioral Therapies, Neuropharmacology, Genetic Mutations, Brain Connectivity,Molecular Mechanisms